2020
DOI: 10.1109/tuffc.2020.3020721
|View full text |Cite
|
Sign up to set email alerts
|

Pilot Study of Robot-Assisted Teleultrasound Based on 5G Network: A New Feasible Strategy for Early Imaging Assessment During COVID-19 Pandemic

Abstract: Early diagnosis is critical for the prevention and control of the coronavirus disease 2019 (COVID-19).We attempted to apply a protocol using teleultrasound, which is supported by the 5G network, to explore the feasibility of solving the problem of early imaging assessment of COVID-19. Four male patients with confirmed or suspected COVID-19 were hospitalized in isolation wards in two different cities. Ultrasound specialists, located in two other different cities, carried out the robot-assisted teleultrasound an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(34 citation statements)
references
References 26 publications
1
33
0
Order By: Relevance
“…Pilot studies showed that 5G-based robot-assisted teleultrasonography is a new feasible strategy for real-time cardiopulmonary assessment during COVID-19 pandemic. 29,30 In these studies, robots replaced the frontline ultrasonographers to obtain the parasternal long-axis view and cardiac apical four-chamber view, and brief echocardiographic assessments were realized. These strategies can help both frontline doctors and remote consultants avoid exposure to the deadly infectious virus.…”
Section: Limitations and Perspectivesmentioning
confidence: 99%
“…Pilot studies showed that 5G-based robot-assisted teleultrasonography is a new feasible strategy for real-time cardiopulmonary assessment during COVID-19 pandemic. 29,30 In these studies, robots replaced the frontline ultrasonographers to obtain the parasternal long-axis view and cardiac apical four-chamber view, and brief echocardiographic assessments were realized. These strategies can help both frontline doctors and remote consultants avoid exposure to the deadly infectious virus.…”
Section: Limitations and Perspectivesmentioning
confidence: 99%
“…They also discuss the technical requirements for enabling these use cases. Wu et al [5] discuss that 5G technologies can be used to enable teleultrasound, in order to prevent infections. They propose an ultrasound protocol based on 5G network to examine the suspected and confirmed COVID-19 patients in epidemic areas.…”
Section: A Communication Technologiesmentioning
confidence: 99%
“…Another system, named OTELO [13] [14], has demonstrated clinical utility in trials [15]. Recent work has even investigated the control of such systems over 5G and in the context of COVID-19 [16].…”
Section: Introductionmentioning
confidence: 99%